2014
DOI: 10.1007/s11162-014-9359-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Merit Aid on Enrollment: A Regression Discontinuity Analysis of Iowa’s National Scholars Award

Abstract: continuum ranging from debt averters to debt accepters. The debt averters avoided debt completely by working and choosing a more impoverished lifestyle. The debt intermediates saw debt as necessary, but something to be minimized. The debt accepters fully accepted the idea of taking out student loans and carrying credit card debt in order to maintain the lavish lifestyle they wanted. Some of the students moved back and forth along the continuum during their college years. (15 ref)-Higher Education and Student A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…A growing number of public universities have developed institutional aid programs that specifically target nonresident students (e.g., Burd, 2015b; DesJardins, 2001; Leeds & DesJardins, 2015). These policies are motivated by the goal of increasing net tuition revenue, as nonresident tuition price is typically more than twice that of resident tuition price, and/or the goal of increasing academic profile, as nonresident students often score higher than residents on college entrance exams (Jaquette, Curs, & Posselt, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A growing number of public universities have developed institutional aid programs that specifically target nonresident students (e.g., Burd, 2015b; DesJardins, 2001; Leeds & DesJardins, 2015). These policies are motivated by the goal of increasing net tuition revenue, as nonresident tuition price is typically more than twice that of resident tuition price, and/or the goal of increasing academic profile, as nonresident students often score higher than residents on college entrance exams (Jaquette, Curs, & Posselt, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although, given that a window of bandwidth around the cut-point a fuzzy RD model could be estimated straightforwardly, it was challenging to choose this bandwidth. The tradeoff between bias and precision was a major motivator of bandwidth selection—larger bandwidths reduced the noisiness of estimates at the expense of introducing bias from data points far from the cutoff for treatment [ 43 ]. To test the robustness of our RD estimation results, besides the sample of the elderly that was aged within 10 years around the 60 cutoff, we also duplicated the estimation procedures by applying samples of elderly aged 52–68 and 48–72.…”
Section: Robustness Checksmentioning
confidence: 99%
“…According to the patterns in the SAT, it is possible to infer that the same situation happens in the ACT sample. Leeds and DesJardins (2015) found their running variable in the Iowa dataset passed the McCrary test, but their running variable was an index associated with the ACT instead of the ACT along. Though the manipulation of the ACT may exist, the other parts in the index, including high school GPA, may reduce the impact from retaking the ACT, making the index less manipulatable.…”
Section: Retaking and Test Score Manipulationmentioning
confidence: 94%
“…To identify the existence of manipulation, the McCrary density test (McCrary, 2008) (including the visual examination of the histogram of the running variable) has been widely suggested and adopted in most articles (Bruce & Carruthers, 2014;Harrington et al, 2016;Leeds & DesJardins, 2015;Scott-Clayton, 2011;Scott-Clayton & Zafar, 2019;Welch, 2014;Zhang et al, 2016). Only studies in Tennessee (Bruce & Carruthers, 2014;Welch, 2014) reported the statistics of the McCrary test.…”
Section: Retaking and Test Score Manipulationmentioning
confidence: 99%
See 1 more Smart Citation